Pembentukan Portfolio Optimal Untuk Berinvestasi pada Saham Perusahaan Perbankan di Bursa Efek Indonesia dengan Metode Sharpe, Treynor dan Jensen Periode 2013-2017 - Wilson Wihardi; Anas Lutfi (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The aim of this research is to find out the performance of the banking company stocks in Indonesia Stock Exchange, and which stocks is the best to form out a portfolio. The measurement in used is Sharpe Index, Treynor Index, and Jensen Index. The object in this research is the 10 banking companies with biggest capitalization in Indonesia Stock exchange due on 31 December 2017 or the last day of trading day in 2017. The conclusion of this research are the best banking company stocks based on Sharpe Indes is BBCA, based on Treynor Index is MEGA, and based on Jensen Index is BJBR. The Optimum Portfolio is consisted of 79,4 % BBCA, 16,9 % MEGA, and 3,7 % BJBR. Expected Return of this portfolio is 18,98 % per year and standard Deviation 7,2 %.